Use of high flow nasal cannula in Spanish neonatal units - Olalla Rodriguez Losada; Alicia Montaner Ramón; Angela Gregoraci Fernández; Vanessa Flores España; Anna Gros Turpin; Juan José Comuñas Gómez; Félix Castillo Salinas (Elsevier, 2022)
Introduction: The use of high-flow cannula therapy (HFNC) in neonatal units has increased in recent years, but there are no consensus guidelines on its indications and application strategies. Our aim was to know the rate of use of HFNC, their indications and the management variability among Spanish neonatal units. Material and methods: Twenty-five-question survey for medical and nursing staff. Level II and III units were contacted by phone and sent in Google forms between September 2016 and December 2018. Results: Ninety-seven responses (63.9% medical, 36.1% nursing), from 69 neonatal units representing 15 autonomous communities (87% level of care III; 13% level II). All units except one have HFNC with a humidified and heated system. Their most frequent indications are: non-invasive ventilation weaning (79.4%), bronchiolitis (69.1%), respiratory distress of the term newborn (58.8%), after extubation (50.5%). Minimum flow (1-5 L/min) and maximum flow (5-15 L/min) are variable between units. 22.7% have experienced some adverse effect from its use (9 air leak, 12 nasal trauma).Less than half have an employment protocol, but all the answers agree on the usefulness of national recommendations. Conclusions: HFNC therapy is widely used in Spanish units, but there is great variability in its indications and strategies of use. National recommendations would be applicable in most units and would allow unifying its use. Resumen: Introducción: El uso de la terapia con cánulas de alto flujo (CNAF) en las unidades neonatales ha experimentado un incremento en los últimos años, pero no existen guías de consenso sobre sus indicaciones y estrategias de aplicación. Nuestro objetivo fue conocer la tasa de empleo de CNAF, sus indicaciones y la variabilidad de uso entre las unidades neonatales españolas. Material y métodos: Encuesta de 25 preguntas dirigida a personal médico y de enfermería. Se contactó telefónicamente con unidades de nivel II y III y se envió en formato Google Forms entre septiembre 2016 y diciembre 2018. Resultados: Se recibieron 97 respuestas (63,9% medicina, 36,1% enfermería), de 69 unidades neonatales que representan a 15 comunidades autónomas (87% nivel asistencial III; 13% nivel II). Todas las unidades, salvo una, disponen de CNAF con sistema humidificado y caliente. Sus indicaciones más frecuentes son: destete de ventilación no invasiva (VNI) (79,4%), bronquiolitis (69,1%), distrés respiratorio del recién nacido a término (RNT) (58,8%), tras extubación (50,5%). El flujo mínimo varía entre 1-5 lpm y el flujo máximo entre 5-15 lpm. El 22,7% ha experimentado algún efecto indeseado por su uso (9 fuga aérea, 12 traumatismo nasal).Menos de la mitad tiene protocolo de empleo, pero todas las respuestas coinciden en la utilidad de unas recomendaciones nacionales. Conclusiones: La terapia con CNAF está ampliamente extendida en las unidades españolas, pero existe gran variabilidad en sus indicaciones y estrategias de utilización. Unas recomendaciones a nivel nacional serían aplicables en la mayoría de las unidades y permitirían unificar su empleo.